ANALISIS KESULITAN SISWA SMA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH PADA MATERI BARISAN DAN DERET DENGAN LANGKAH-LANGKAH MENURUT POLYA - Yana Pirmanto; Muhamad Farid Anwar; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to analyze the difficulties of high school students in solving problems based on solving the material sequence and sequence with stages according to Polya. This type of research is a qualitative descriptive study. The analysis was carried out by giving a written test in the form of a question description with a total of 5 questions and interviews, then analyzing the results of tests and interviews with students. The method of data collection is done by a painted test accompanied by an interview. The results of the analysis show that: (1) students' ability to understand problems is low, that is around 28%, (2) ability to plan low resolution around 32%, (3) ability to solve problems very low around 16%, (4) ability to re-examine very low which is around 8%.